High‐Order Soliton Solution of Landau–Lifshitz Equation. Issue 2 (6th September 2014) - Bian, Dongfen; Guo, Boling; Ling, Liming
<x xml:space="preserve">Abstract</x> The Landau–Lifshitz equation is analyzed via the inverse scattering method. First, we give the well‐posedness theory for Landau–Lifshitz equation with the frame of inverse scattering method. The generalized Darboux transformation is rigorous considered in the frame of inverse scattering transformation. Finally, we give the high‐order soliton solution formula of Landau–Lifshitz equation and vortex filament equation.